Kajian Literatur : Perlindungan Hukum Terhadap Korban Revenge Porn - Sahira Azzahra; Atika Fitriani; Erma Nuril Fajria; Mivtahul Janati Rahmi Fajri; Sarifah Aini Hasibuan; Ilham Hudi (Lembaga Pengembangan Kinerja Dosen, 2024)
Gender inequality, sexual violence, domestic violence, trafficking in women, and wartime exploitation are some of the many human rights violations that occur. With the advancement of information technology and globalization, the use of violence has changed and evolved. Revenge pornography, also known as